Optical coherence tomography Angio-B mode for early detection of myopic choroidal neovascularization and treatment with Bevacizumab - Rico, Stephanie (2024)
Purpose The purpose of this case report is to outline the management of a 41-year-old female with pathological myopia and type II choroidal neovascularization (CNV) diagnosed by optical coherence tomography angiography (OCT-A) angio-B mode. Observations The early detection of CNV with OCT-A angio-B mode and treatment with intra-vitreous injections of Bevacizumab contributed to the amelioration of her vision to 20/20, a better visual acuity than she had prior to treatment. Conclusions and importance This case report suggests that an OCT-A scan may reveal the initial formation of abnormal vasculature before pathological changes are evident in structural OCT, allowing for prompt treatment and resolution in patients with myopic CNV.